Learning anywhere, anytime through a laptop: a pilot study in a secondary school. - Moura, Adelina (2013)
The reduction in the cost of laptops has increased their use and they have become a real tool in the teaching and learning process, making possible the development of true life-long learning abilities in young people. The young people of today have grown up with advanced technologies and spend a large part of their time using them. This fact allowed us to carry out a pilot study with laptops connected to the Internet, one-to-one, with students of Professional School. This study took place in the third term of 2005/2006, and data collection was by questionnaires, interview and log book. The results show a positive impact of the laptops in relation to motivation, group work, research and the communicative interaction. However, some pupils said that the laptop is a tool which will provide a high level of disturbanc